HUBUNGAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI PADA SISWA KELAS XI SMA NEGERI 1 BERASTAGI - Julius Boy Nesra Basgimata Barus; Janwar Frihasan Sinuraya (Universitas Quality, 2021)
Motivation is an impulse that comes from within a person to be able to manifest actions in producing a goal. As for the urge to do something, it can achieve certain needs. Learning outcomes are abilities that are contained in students that will be obtained from students from experience during learning. The purpose of this study was to analyze the relationship between learning motivation and learning outcomes of physical education in class XI students of SMA Negeri 1 Berastagi. The method used in this research is quantitative descriptive quantitative method. Data collection techniques used in this study using the google form application. This research is a study involving a sample with a population of 35 students. The data analysis technique used is the product moment correlation. The results showed that: (1) the average / mean learning motivation of class XI SMA Negeri 1 Berastagi was 60.77 or in the moderate category, (2) the average / mean learning outcomes of class XI SMA Negeri 1 Berastagi was 80 , 77 or in the moderate category, and (3) there is a positive and significant relationship between learning motivation and learning outcomes in the Physical Education Subject of Class XI Students of SMA Negeri 1 Berastagi. This is indicated by the magnitude of the calculated r value is greater than r table (0.512> 0.375) and the significance value is 0.000, which means less than 0.05 (0.000 <0.05).